Taṭwīr Ta`līm Mahārah al-Qirā‘ah Bi Ṭarīqah “Anṭiq Wa Mayyiz” `Alā Asās al-Madkhal as-Siyāqī Wa al-Madkhal al-Binā‘ī Bi MIN 9 Aceh Selatan: MIN 9 Aceh Selatan تطوير تعليم مهارة القراءة بطريقة "انطق وميّز" على أساس المدخل السياقي والمدخل البنائي بــ - Farhana, Ana; Hilmi, Hilmi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Based on the observation of the first-in-class fourth of the Government Islamic Primary School 9 South Aceh students are weak in pronouncing words and sentences in the text and students find it difficult to pronounce letters in Arabic words and have difficulty distinguishing the correct pronunciation. This also makes them feel weak in mastering the meaning of vocabulary and unable to understand the text. When the teacher distributes to groups and asks students to pronounce the words in the text and asks students to take turns reading they find it difficult to read. In the teaching and learning process, students cannot answer the teacher's questions about the text. With these problems, researchers want to develop learning reading skills with the "Intiq Wa Mayyiz" method based on the CTL approach and the constructivism approach. The purpose of this thesis is to identify the student's response, the validation of experts, and the effectiveness of developing the teaching of reading skills in an " Intiq Wa Mayyiz " manner, on the basis of a contextual approach and a constructivist approach. In this study, researchers used research and development methods with the type of One Group Pre-test and Post-test Design. The researcher presented questionnaires, pre-tests, and post-tests as research tools. As for the results of the research, the development of teaching reading skills using the "Intiq Wa Mayyiz" method has a positive response among students, and the researchers found their response results to be very good because this method can improve students' abilities, tendencies and desires in reading skills. The validity assessed by experts in teaching reading skills using the "Intiq Wa Mayyiz" method obtained a result of good and pleasant traits. The development of teaching reading skills using the "Intiq Wa Mayyiz" method is effective for improving reading skills.